RESULTS OF TWO-YEARS’ SEISMO-HYDROLOGICAL MONITORING IN THE AREA OF THE HRONOV-POřÍČÍ FAULT ZONE, WESTERN SUDETES - Stejskal V.; Skalský L.; Kašpárek L. (My University, 2007)
We present first results of the study of possible relations between the seismic activity and crustal fluids (groundwater andcarbon dioxide) in the area of the Hronov-Poříčí Fault Zone (HPFZ), situated on the NE margin of the Bohemian Massif. Local seismic monitoring and observations of groundwater levels in deep wells and concentrations of carbon-dioxide in the mineral spring at Třtice was started in 2005. Since then, more than 30 local seismic events were observed in the area of the HPFZ. The two strongest earthquakes with macroseismic effects were recorded on August 10, 2005 (M = 2.4) and October25, 2005 (M = 3.3). Most of the epicentres were situated along the central part of the HPFZ. Only some weak events fromFebruary and March 2006 were concentrated along the SE termination of the HPFZ. Results of the hydrological monitoringshow that water level fluctuations are affected mainly by the precipitation, snow-melt, air pressure changes, and tidal deformations of the Earth’s crust. The effects of seismo-tectonic activity were detected only in one out of five water wells, where we observed several step-like water level anomalies with amplitudes of 4 to 15 cm. Two of them preceded the August10, 2005 and October 25, 2005 earthquakes. Three other anomalies seemed to originate independently of the seismic activity.We therefore suppose that they were induced by aseismic movements along the HPFZ. Contrary to the water level fluctuations, CO2 concentrations in the mineral spring seem to be dependent on water temperature; no evident seismic-induced changes have been observed yet.
Keywords: CRUSTAL DEFORMATION; EARTH TIDES; EARTHQUAKE PRECURSORS; GROUNDWATER; HRONOV-POřÍČÍ FAULT ZONE; SEISMIC ACTIVITY